A training on cold wax batik in Bakungan Village, Kutai Kartanegara Regency - Etwin Fibrianie Soeprapto; Dwi Cahyadi; Rinto Dwi Atmodjo (Community Empowerment, 2021)
Batik is the nation's cultural heritage which functions as a formal attire as well as a medium for delivering non-verbal messages to users. Indonesia is recognized by UNESCO as the owner of batik culture. Currently, there is an innovation about cold wax that can be used for batik, where the results are as good as hot wax batik and more environmentally friendly. This community service activity raised the theme of cold wax batik training for the Cakra Borneo community in Bakungan Village, Loa Janan District, Kutai Kartanegara Regency, East Kalimantan. This activity was organized with partners, namely Borneo Craft Indonesia, batik craftsmen who will help transfer knowledge about cold wax batik. Through this training, participants are able to improve their abilities in producing East Kalimantan batik works that will make city branding a candidate for the capital city of Indonesia.